The "Healthy smile" - Rosa María González Ramos; María Isabel Ventura Hernández; Jorge Raúl Valdivié Provance; Cecil Regla Serrano Álvarez (Editorial Ciencias Médicas, 2014)
Introduction: educational programs play an important role in the modification of harmful habits and behavior. Elderly persons should acquire the knowledge required for oral self-care, thus improving their quality of life. Objective: evaluate the results of the "Healthy smile" program. Methods: adescriptive cross-sectional study was conducted with a universe of 74 persons aged 60 and over. The variables considered were age and sex. The data obtained were organized on the basis of the following criteria: knowledge about oral and general health, main oral and dental diseases, performance of the oral self-examination, effects of smoking and alcoholism, intake of sugared, hot and spicy foods, and the importance of oral hygiene. Data collection was performed by the authors based on a questionnaire applied during the first stage of the research and using absolute values and percentages for the analysis of results. Results: the 70-79 age group and female sex are the best represented variables, with 36.5 % and 59.5 %, respectively. Knowledge about the harmful effects of the following actions behaved in the manner indicated: alcoholism 91.9 %, smoking 95.9 %, intake of sugared foods 97.7 % and intake of hot and spicy foods 90.5 %. Knowledge about oral self-examination and oral hygiene was 78.4 and 91.9 %, respectively. Conclusions: the "Healthy smile" educational program was effective to broaden the knowledge of elderly persons about the activities included in the program.